Inclusão de Estudantes Autistas em uma escola regular de ensino em Floriano/PI: indicadores para intervenção institucional - ROCHA, Luciana Alves (2023)
Recent educational policies have been guiding the inclusion of autistic students in regular schools, which has led to changes in educational practices and paradigms. More specifically, students with Autism Spectrum Disorder (ASD) have had their rights expanded in relation to social and educational inclusion, which has reconfigured new challenges for the areas that address this issue.